Intensity interferometry of P Cygni in the H α emission line: towards distance calibration of LBV supergiant stars. Issue 1 (27th February 2020) - Rivet, J-P; Siciak, A; de Almeida, E S G; Vakili, F; Domiciano de Souza, A; Fouché, M; Lai, O; Vernet, D; Kaiser, R; Guerin, W
ABSTRACT: We present intensity interferometry of the luminous blue variable P Cyg in the light of its H α emission performed with 1 m-class telescopes. We compare the measured visibility points to synthesized interferometric data based on the CMFGEN physical modelling of a high-resolution spectrum of P Cyg recorded almost simultaneously with our interferometry data. Tuning the stellar parameters of P Cyg and its H α linear diameter, we estimate the distance of P Cyg as 1.56 ± 0.25 kpc, which is compatible within 1σ with 1.36 ± 0.24 kpc reported by the Gaia DR2 catalogue of parallaxes recently published. Both the values are significantly smaller than the canonic value of 1.80 ± 0.10 kpc usually adopted in literature. Our method used to calibrate the distance of P Cyg can apply to very massive and luminous stars both in our Galaxy and neighbouring galaxies, and can improve the so-called wind momentum–luminosity relation that potentially applies to calibrate cosmological candles in the local Universe.